2003
DOI: 10.1126/science.1088208
|View full text |Cite
|
Sign up to set email alerts
|

CB1 Cannabinoid Receptors and On-Demand Defense Against Excitotoxicity

Abstract: Abnormally high spiking activity can damage neurons. Signaling systems to protect neurons from the consequences of abnormal discharge activity have been postulated. We generated conditional mutant mice that lack expression of the cannabinoid receptor type 1 in principal forebrain neurons but not in adjacent inhibitory interneurons. In mutant mice,the excitotoxin kainic acid (KA) induced excessive seizures in vivo. The threshold to KA-induced neuronal excitation in vitro was severely reduced in hippocampal pyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
948
5
14

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,111 publications
(1,032 citation statements)
references
References 38 publications
50
948
5
14
Order By: Relevance
“…This includes in vivo models of maximal electroshock in mice (Wallace et al, 2001) and the pilocarpine model in rats (Wallace et al, 2003), and in vitro, in hippocampal neuronal culture models of acquired epilepsy and status epilepticus (Blair et al, 2006). Moreover, endocannabinoids such as AEA and 2-AG have been shown to exhibit neuroprotective effects (Marsicano et al, 2003) and antiepileptic effects when applied exogenously (Wallace et al, 2002). In addition, it has been demonstrated that prolonged febrile seizures enhanced endocannabinoid-mediated depolarizationinduced suppression of inhibition (DSI) (Chen et al, 2003;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes in vivo models of maximal electroshock in mice (Wallace et al, 2001) and the pilocarpine model in rats (Wallace et al, 2003), and in vitro, in hippocampal neuronal culture models of acquired epilepsy and status epilepticus (Blair et al, 2006). Moreover, endocannabinoids such as AEA and 2-AG have been shown to exhibit neuroprotective effects (Marsicano et al, 2003) and antiepileptic effects when applied exogenously (Wallace et al, 2002). In addition, it has been demonstrated that prolonged febrile seizures enhanced endocannabinoid-mediated depolarizationinduced suppression of inhibition (DSI) (Chen et al, 2003;.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoid compounds have been reported to exhibit both antiepileptic (Blair et al, 2006;Wallace et al, 2001; and neuroprotective properties (Marsicano et al, 2003) via cannabinoid receptors. The endogenous cannabinoid (endocannabinoid) system is integral in controlling neuronal excitability and synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…49 A downregulation of BDNF in the hippocampus, for example, is believed to correlate with depression-like behavior, and injections of BDNF into the hippocampus have been demonstrated to lead to decreased floating in the FST. 37 As we could recently demonstrate that endocannabinoid signaling via CB1 receptors regulates BDNF expression, 2,43 we investigated BDNF mRNA expression in the hippocampus of CB1 À/À and CB1 þ / þ mice. In situ hybridization revealed a specific downregulation of BDNF mRNA in the CA3 region of the hippocampus of CB1 À/À mice (Figure 7), which might, thus, be related to the depression-like FST phenotype in CB1 À/À mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although CNS CB1R KO mice have not been reported, CB1R KO in a subpopulation of neurons has been reported. 51 The latter is not appropriate to address the site-of-action question because not all CB1R's are removed from the CNS.…”
Section: Peripheral Physiological Effects Vs Peripheral Site Of Actiomentioning
confidence: 99%